Pemberian Jus Buah (Etlingera hemisphaerica) terhadap Pemulihan Eritrosit dan Leukosit Akibat Perlakuan Merkuri Klorida (HgCl2) pada Mencit (Mus musculus) - Fatimah Azzahrah; Aceng Ruyani; Deni Parlindungan; Arsela Eko Listiono; Afrizal Mayub (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to determine the effect of Etlingera hemisphaerica (honje) fruit juice on the recovery of erythrocyte and leukocyte counts in mice (Mus musculus) exposed to mercuric chloride (HgCl₂). The method used was an experimental design using male mice as test animals, divided into three groups: K1 (control), K2 (honje juice 0.3 mL/20 g BW for 3 days), and K3 (HgCl₂ 5 mg/kg BW + honje juice 0.3 mL/20 g BW for 3 days). The observed parameters were the number of erythrocytes and leukocytes before and after treatment. The results showed that honje juice administration increased the erythrocyte count in group K2, while in group K3, erythrocyte recovery was affected by mercury exposure, making the honje juice less effective, although the values remained within the normal range compared to the control group. In leukocyte count, group K2 showed a stabilizing effect, whereas group K3 experienced an increase due to HgCl₂ exposure. In conclusion, Etlingera hemisphaerica fruit juice has potential as a phytotherapy agent to repair hematological damage caused by heavy metal toxicity, although its effectiveness is influenced by the metabolic condition of the mice and the high concentration of mercury. Keywords: Etlingera hemisphaerica, Erythrocytes, Leukocytes, Mice, Mercuric Chloride